2021
DOI: 10.1590/1980-220x-reeusp-2020-0458
|View full text |Cite
|
Sign up to set email alerts
|

Women’s alcohol consumption in a Primary Health Care service

Abstract: Objective: To identify alcohol consumption patterns in people cared by a Primary Health Care service and verify the association between the patterns and the variables of the sample. Method: Our observational study used both the Alcohol Use Disorders Identification Test instrument and a questionnaire with socio-demographic, clinical, and behavioral questions for data collection. We carried out the descriptive and univariate analysis with Kendall and Kruskal-Wallis correlation tests. We introduced variables wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Alcohol and tobacco consumption among women used to occur in small frequencies and volumes, when compared to men. However, changes in the social role of women over time show that there has been an adoption of habits previously considered masculine 44 and this change is more evident among younger women 45 . A study carried out in primary care, with women, suggests that higher alcohol consumption is associated with a greater load of emotional, stress such as prejudice, discrimination, and violence, experienced due to sexual orientation or the accumulation of functions among those who are single mothers 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol and tobacco consumption among women used to occur in small frequencies and volumes, when compared to men. However, changes in the social role of women over time show that there has been an adoption of habits previously considered masculine 44 and this change is more evident among younger women 45 . A study carried out in primary care, with women, suggests that higher alcohol consumption is associated with a greater load of emotional, stress such as prejudice, discrimination, and violence, experienced due to sexual orientation or the accumulation of functions among those who are single mothers 45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in the social role of women over time show that there has been an adoption of habits previously considered masculine 44 and this change is more evident among younger women 45 . A study carried out in primary care, with women, suggests that higher alcohol consumption is associated with a greater load of emotional, stress such as prejudice, discrimination, and violence, experienced due to sexual orientation or the accumulation of functions among those who are single mothers 45 . However, a study on protective behavior strategies showed that women have a healthier style and consumption of alcohol than men 46 .…”
Section: Discussionmentioning
confidence: 99%